Evaluation of reproductive performance of holstein friesian cattle in Sabah, Malaysia - Nezzy Suzie Nelson
The reproductive performance of Holstein Friesian cattle in Desa Dairy Farm in Sabah, Malaysia was evaluated. Twenty percent of 244 total population cows were selected and their reproductive data from 2011 to 2012 were gathered and analysed for the pregnancy rate, calving interval and calving rate. There performance indices were then compared with published benchmarks for each index (Pregnancy rate; 70% - 80%; Calving rate: 95.6%; and Calving internal: 360 – 390 days). This farm had recorded higher pregnancy rate of 88%, lower calving rate of 91%, and longer calving interval of 399 days compared to the benchmarks. The findings suggest that the reproductive performance of the studied farm could be related to the environmental temperature and farm management practices.